The “indiviso” of the clergy. Living conditions of the lower secular clergy of Barcelona in 1698 - Fernández Terricabras, Ignasi (Cuadernos de Historia Moderna, 2021)
The article is a statistical analysis of a list of 321 ecclesiastics who were part of the lower clergy of the city of Barcelona in 1698, distributed in eleven institutions, of which seven were parishes. The document is a fiscal source that identifies the living conditions of each ecclesiastic. Therefore, it allows individual and inter-church comparisons to be made that show the great diversity of situations among the lower clergy of Barcelona and, at the same time, some singularities compared to other Spanish regions.